Histone deacetylases modulate resistance to the therapy in lung cancer - Contreras-Sanzón, Estefanía; Prado-Garcia, Heriberto; Romero-Garcia, Susana; Nuñez-Corona, David; Ortiz-Quintero, Blanca; Luna-Rivero, Cesar; Martínez-Cruz, Victor; Carlos-Reyes, Ángeles (Frontiers in Genetics, 2022)
The acetylation status of histones located in both oncogenes and tumor suppressor genes modulate cancer hallmarks. In lung cancer, changes in the acetylation status are associated with increased cell proliferation, tumor growth, migration, invasion, and metastasis. Histone deacetylases (HDACs) are a group of enzymes that take part in the elimination of acetyl groups from histones. Thus, HDACs regulate the acetylation status of histones. Although several therapies are available to treat lung cancer, many of these fail because of the development of tumor resistance. One mechanism of tumor resistance is the aberrant expression of HDACs. Specific anti-cancer therapies modulate HDACs expression, resulting in chromatin remodeling and epigenetic modification of the expression of a variety of genes. Thus, HDACs are promising therapeutic targets to improve the response to anti-cancer treatments. Besides, natural compounds such as phytochemicals have potent antioxidant and chemopreventive activities. Some of these compounds modulate the deregulated activity of HDACs (e.g. curcumin, apigenin, EGCG, resveratrol, and quercetin ). These phytochemicals have been shown to inhibit some of the cancer hallmarks through HDACs modulation. The present review discusses the epigenetic mechanisms by which HDACs contribute to carcinogenesis and resistance of lung cancer cells to anticancer therapies.